Inhibition of Rous sarcoma virus replication and cell transformation by a specific oligodeoxynucleotide. - Zamecnik, P C (1978)
The tridecamer d(A-A-T-G-G-T-A-A-A-A-T-G-G), which is complementary to 13 nucleotides of the 3'- and 5'-reiterated terminal sequences of Rous sarcoma virus 35S RNA, was added to chick embryo fibroblast tissue cultures infected with Rous sarcoma virus. Inhibition of virus production resulted. The inference emerges that the tridecamer and its counterpart with blocked 3'- and 5'-hydroxyl termini enter the chick fibroblast cells, hybridize with the terminal reiterated sequences at the 3' and 5' ends of the 35S RNA, and interfere with one or more steps involved in viral production and cell transformation. Likely sites of action are (i) the circularization step of the proviral DNA intermediate, and (ii) the initiation of translation, the latter being described in the following communication [Stephenson, M. L. & Zamecnik, P. C. (1978) Proc. Natl. Acad. Sci. USA 75, 285--288].